Highly Efficient Yellow Organic Light Emitting Diode with a Novel Wet‐ and Dry‐Process Feasible Iridium Complex Emitter. (5th August 2013) - Jou, Jwo‐Huei; Lin, You‐Xing; Peng, Shiang‐Hau; Li, Chieh‐Ju; Yang, Yu‐Min; Chin, Chih‐Lung; Shyue, Jing‐Jong; Sun, Shih‐Sheng; Lee, Mandy; Chen, Chien‐Tien; Liu, Ming‐Chung; Chen, Cheng‐Chang; et al.
<x xml:space="preserve">Abstract</x> Yellow emission is crucial in RGBY display technology and in fabricating physiologically friendly, low color‐temperature lighting sources. Emitters with both wet‐ and dry‐process feasibility are highly desirable to fabricate, respectively, high‐quality devices via vapor deposition and cost‐effective, large‐area devices via roll‐to‐roll fabrication. Here, high‐efficiency organic light‐emitting diodes with a novel wet‐ and dry‐process feasible yellow‐emitting iridium complex, bis[5‐methyl‐7‐fluoro‐5H‐benzo(c)(1, 5) naphthyridin‐6‐one]iridium (picolinate), are demonstrated. By spin coating, the device shows, at 1000 cd m−2, an external quantum efficiency (EQE) of 18.5% with an efficacy of 52.3 lm W−1, the highest among all reported yellow devices via wet‐process, while using vapor deposition, the EQE is 22.6% with a 75.1 lm W−1 efficacy, the highest among all dry‐processed counterparts. The high efficiency may be attributed to the replacement of the hydrogen atom with a fluorine atom on a 2‐substitutional site in the emitter to prevent dense molecular packing‐caused self‐quenching and to reduce radiationless deactivation rates, leading to a high quantum yield (71%).